Fructose promotes pyoluteorin biosynthesis via the CbrAB-CrcZ-Hfq/Crc pathway in the biocontrol strain Pseudomonas PA1201 - Cui, Ying; Song, Kai; Jin, Zi Jing; Lee, Learn Han; Thawai, Chitti; He, Ya Wen (My University, 2023)
Biocontrol strain Pseudomonas PA1201 produces pyoluteorin (Plt), which is an antimicrobial secondary metabolite. Plt represents a promising candidate pesticide due to its broad-spectrum antifungal and antibacterial activity. Although PA1201 contains a complete genetic cluster for Plt biosynthesis, it fails to produce detectable level of Plt when grown in media typically used for Pseudomonas strains. In this study, minimum medium (MM) was found to favor Plt biosynthesis. Using the medium M, which contains all the salts of MM medium except for mannitol, as a basal medium, we compared 10 carbon sources for their ability to promote Plt biosynthesis. Fructose, mannitol, and glycerol promoted Plt biosynthesis, with fructose being the most effective carbon source. Glucose or succinic acid had no significant effect on Plt biosynthesis, but effectively antagonized fructose-dependent synthesis of Plt. Promoter-lacZ fusion reporter strains demonstrated that fructose acted through activation of the pltLABCDEFG (pltL) operon but had no effect on other genes of plt gene cluster; glucose or succinic acid antagonized fructose-dependent pltL induction. Mechanistically, fructose-mediated Plt synthesis involved carbon catabolism repression. The two-component system CbrA/CbrB and small RNA catabolite repression control Z (crcZ) were essential for fructose-induced Plt synthesis. The small RNA binding protein Hfq and Crc negatively regulated fructose-induced Plt. Taken together, this study provides a new model of fructose-dependent Plt production in PA1201 that can help improve Plt yield by biosynthetic approaches.
Keywords: Biocontrol; Carbon catabolism repression; Fructose; Pseudomonas; Pyoluteorin